P823 Effects of smoking cessation in IBD: Insights from the Swiss IBD Cohort study (SIBCS). (16th January 2018) - Martinho-Grueber, M; Biedermann, L; Vavricka, S; Schöpfer, A; Clair Willi, C; Fournier, N; Allez, M; Macpherson, A J; Juillerat, P
Abstract: Background: Smoking strongly affects the course of disease in patients with inflammatory bowel disease (IBD). Smoking is a risk factor for Crohn's disease (CD) and worsens the course of the disease by increasing the rate of relapses, need for immunosuppressants and surgery. On the contrary, tobacco consumption is rather protective in ulcerative colitis (UC). Therefore, smoking cessation in CD leads to an early reduction of flares (in the first 3 months), a more benign course and less medical therapy. 1, 2 Our aim was to evaluate the effect of smoking cessation in UC and CD patients of the Swiss IBD Cohort study (SIBDCS). Methods: Adult IBD patients were prospectively included in the Swiss IBD cohort from November 2006 to November 2015. They were asked about their smoking status at enrolment and during the follow-up. We identified active smokers with a change of smoking status during follow-up suggesting a successful cessation of tobacco consumption and matched them to a group of patients continuing to smoke, Results: A total of 2367 IBD patients (1368 CD, 999 UC) were included in the analysis. We identified 125 CD and 40 UC active smokers ceasing tobacco consumption during the follow-up there were matched to 214 CD and 50 UC smokers for gender, age at diagnosis and age. Among CD patients, smoking cessation was protective against the progression to fistulising disease (OR = 2.2, p < 0.05), whereas, there was no association with increasing numbers of flares, stenosing behaviour or surgeries. Among UC patients, persistent smokers developed more extra-intestinal manifestations than quitters (OR = 2.4, p = 0.09), this was also present at lower level in CD (OR = 1.2). Conclusions: Our findings in the Swiss IBD Cohort study are align with the literature: a reduction of the risk of fistulas among CD patients quitting smoking and the association between extraintestinal manifestations and aktive smoking status in IBD patients. 3 References: 1. Cosnes et al. Smoking cessation and the course of Crohn's disease: an intervention study. Gastroenterology, 2011. 2. Nunes T, et al . Impact of smoking cessation on the clinical course of Crohn's disease under current therapeutic algorithms: a multicenter prospective study. Am J Gastroenterol, 2016. 3. Severs M et al. Smoking is associates with extraintestinal manifestations in IBD. J Crohn Colitis, 2016.